1991
DOI: 10.1111/j.1365-2958.1991.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and sequence of the rfb (O antigen) gene cluster of Salmonella serovar typhimurium (strain LT2)

Abstract: The rfb gene cluster of Salmonella LT2 has been cloned and sequenced. The genes rfbA, rfbB, rfbD, rfbF, rfbG, rfbK, rfbM and rfbP were located individually and the gene rfbL was located outside the cluster. Approximately 16 open reading frames were found in the region which is essential for the expression of O antigen. The gene products of rfbB and rfbG were found to have homology with the group of dehydrogenase and related enzymes described previously. Analysis of the G + C ratio of the rfb cluster extended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
355
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(376 citation statements)
references
References 55 publications
17
355
0
3
Order By: Relevance
“…At the same time, Southern blot analysis was performed to characterize the conservation of the 17 O-antigen genes of A. hydrophila PPD134/91 across the 23 A. hydrophila strains. The results are summarized in 18), and its DNA sequences were determined. The whole O-antigen cluster for JCM3980 was determined to be 17,297 bp long (positions 2155 to 19451 in accession no.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Southern blot analysis was performed to characterize the conservation of the 17 O-antigen genes of A. hydrophila PPD134/91 across the 23 A. hydrophila strains. The results are summarized in 18), and its DNA sequences were determined. The whole O-antigen cluster for JCM3980 was determined to be 17,297 bp long (positions 2155 to 19451 in accession no.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted gene products of epsD, epsE, epsF, epsG, and epsH from L. lactis are homologous to glycosyltransferases. CpsE from Streptococcus pneumoniae, ExoY from Rhizobium meliloti, and RfbP from Salmonella enterica are involved in the linkage of the first sugar of the repeating unit to the undecaprenylphosphate carrier (Rubens et al, 1993;Kolkman et al, 1996;Reuber and Walker, 1993;Jiang et al, 1991;Wang and Reeves, 1994). For RfbP (WbaP), it has been demonstrated that the glycosyltransferase activity is encoded in the C-terminal half of the protein and that the N-terminal half is involved in a later step in biosynthesis (Wang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins found to be homologous to EpsD (Table 2) are involved in linking the first sugar of the repeating unit to the lipid carrier (Rubens et al, 1993;Kolkman et al, 1996;Reuber and Walker, 1993;Jiang et al, 1991;Wang and Reeves, 1994). Therefore, it may be expected that EpsD will also act as a glycosyltransferase linking either glucose or galactose to the lipid carrier.…”
Section: The Gene Epsd Is Essential For Eps Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…2): one group collects the K258-containing putative aminotransferases, the second the PMP-dependent dehydrases containing the histidine, and the third coincides with YIFI-ECOLI, which has K258 but other peculiarities not yet well understood. Dhillon et al, 1989Takagi et al, 1990Stutzman-Engwall et al, 1992Lacalle et al, 1992Distler et al, 1992Jiang et al, 1991Daniels et al, 1992Thorson et al, 1993Thorson et al, 1993 a Available SWISS-PROT codes.…”
Section: Y H G V S L W a E R L S Q E L L A L P S H P G L H L D Hmentioning
confidence: 99%